2018
DOI: 10.1101/382846
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Insights from Comparison of the Renal and Skin Single Cell Transcriptomes in Lupus Nephritis

Abstract: Lupus nephritis (LN) occurs in up to 50% of patients with systemic lupus erythematosus (SLE), and is a major contributor to mortality and morbidity. LN presents as a highly heterogeneous disease both in histopathology and response to therapy. The molecular and cellular processes leading to renal damage and to the heterogeneity of the disease are not well understood. To elucidate the processes underpinning the heterogeneity of LN, we applied singlecell RNA-sequencing (scRNA-seq) to renal biopsies from LN patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Preliminary analysis of small numbers of LN patients with available follow-up data found that tubular cells from patients who did not respond to conventional therapy at 6 months post biopsy showed a higher IFN score and increased expression of genes encoding extracellular matrix (ECM) proteins and ECM interaction proteins, suggesting a fibrotic process. A trend toward up-regulation of both ECM pathways was also observed in keratinocytes of nonresponders (32). Exploration of the cellular interactions between various cell types in the kidney and skin suggest that the fibrotic process may be mediated through fibroblast growth factor receptors on the tubular cells whose ligand is expressed in leukocytes.…”
mentioning
confidence: 89%
“…Preliminary analysis of small numbers of LN patients with available follow-up data found that tubular cells from patients who did not respond to conventional therapy at 6 months post biopsy showed a higher IFN score and increased expression of genes encoding extracellular matrix (ECM) proteins and ECM interaction proteins, suggesting a fibrotic process. A trend toward up-regulation of both ECM pathways was also observed in keratinocytes of nonresponders (32). Exploration of the cellular interactions between various cell types in the kidney and skin suggest that the fibrotic process may be mediated through fibroblast growth factor receptors on the tubular cells whose ligand is expressed in leukocytes.…”
mentioning
confidence: 89%
“…Single-cell RNA-sequencing (scRNA-seq) is a powerful technique that enables gene expression measurements in thousands of individual cells. Resolving cellular heterogeneity by scRNA-seq has enabled groundbreaking discovery in the biomedical domain, such as finding key disease drivers in cancer 1-3 , neurodegeneration 4,5 and immune-mediated diseases [6][7][8][9] . From a data analysis standpoint, a crucial step in a standard scRNA-seq pipeline 10 is clustering, where discrete cell populations sharing a common transcriptional profile are defined.…”
Section: Introductionmentioning
confidence: 99%